2021
DOI: 10.3389/fpubh.2021.648054
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Diagnostic Delays in Human Brucellosis in Tongliao City, Inner Mongolia Autonomous Region, China

Abstract: The diagnostic delays pose a huge challenge to human brucellosis (HB), which increases the risk of chronicity and complications with a heavy disease burden. This study aimed to quantify and identify the associated factors in the diagnostic delays to its prevention, reduction, and elimination. This study analyzed risk factors associated with the diagnostic delays in a cross-sectional study with data collected from Tongliao City, Inner Mongolia Autonomous Region of China. Diagnostic delays were defined with a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The slow growth of Brucella in primary cultures delays diagnosis. Therefore, serological tests play a major role in the routine diagnosis of brucellosis [27] , [43] . This was evident in our study when the initial 54 blood cultures of symptomatic patients showed no growth.…”
Section: Discussionmentioning
confidence: 99%
“…The slow growth of Brucella in primary cultures delays diagnosis. Therefore, serological tests play a major role in the routine diagnosis of brucellosis [27] , [43] . This was evident in our study when the initial 54 blood cultures of symptomatic patients showed no growth.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions and screening of travelers, especially with fever and similar symptoms, likely reduced the number of nonlocal cases visiting Xi'an for treatment (36). Additionally, shorter HB-diagnostic delays were observed at CDC agencies probably because of their better laboratory testing capabilities, which underlies their significance in the prevention and control of infectious diseases (24).…”
Section: Discussionmentioning
confidence: 99%
“…Farmers, herdsmen, and abattoir workers were classified as rural workers, while other occupations such as healthcare workers, students, and teachers were defined as non-rural workers. Diagnostic delays were defined as the time interval between the onset of HB symptoms noted by the patient and its confirmed diagnosis at a healthcare institution (24).…”
Section: Human Brucellosismentioning
confidence: 99%
“…Although it is rarely fatal, diagnostic challenges such as nonspecific clinical signs and slow growth in culture specimens, which result in a delayed diagnosis, lead to severe disabilities. 11 Therefore, the objective of this study was to establish the frequency, clinical manifestations, and para-clinical characteristics of brucellar arthritis and sacroiliitis in patients presenting to a referral hospital in the west of Iran.…”
Section: Introductionmentioning
confidence: 99%